Carotid sinus hypersensitivity associated with focal α-synucleinopathy of the autonomic nervous system. Issue 9 (16th August 2006) - Polvikoski, T; Kalaria, R N; Perry, R; Miller, V; Kenny, R A
Abstract : A case of an 82-year-old woman who experienced repeated falls is described. She exhibited a cardioinhibitory carotid sinus hypersensitivity after right carotid sinus massage (CSM), but without evidence of orthostatic hypotension. After a pacemaker was implanted, she did not experience any falls, dizziness or syncope. Her balance eventually deteriorated, but she remained cognitively intact and died from lung cancer at the age of 89 years. Neuropathological examination showed only age-related Alzheimer's disease pathology and a few α-synuclein-positive granular deposits and neurites in the dorsal nucleus of the vagus and solitary tract nucleus in the medulla, but a marked α-synuclein pathology in the stellate ganglia. The cardioinhibitory element of her CSM was possibly because of the α-synuclein pathology in the ganglion, which impaired sympathetic transmission. This case shows another phenotype among patients with α-synucleinopathy.